Blood, lead and spheres: A hindered settling equation for sedimentologists based on metadata analysis. (16th February 2022) - Baas, Jaco H.; Baker, Megan L.; Buffon, Patricia; Strachan, Lorna J.; Bostock, Helen C.; Hodgson, David; Eggenhuisen, Joris T.; Spychala, Yvonne T.
Abstract: A revision of the popular equation of Richardson and Zaki (1954a, Transactions of the Institute of Chemical Engineering, 32, 35–53) for the hindered settling of suspensions of non‐cohesive particles in fluids is proposed, based on 548 data sets from a broad range of scientific disciplines. The new hindered settling equation enables predictions of settling velocity for a wide range of particle sizes and densities, and liquid densities and viscosities, but with a focus on sediment particles in water. The analysis of the relationship between hindered settling velocity and particle size presented here shows that the hindered settling effect increases as the particle size decreases, for example, a 50% reduction in settling velocity is reached for 0.025 mm silt and 4 mm pebbles at particle concentrations of 13% and 25% respectively. Moreover, hindered settling starts to influence the settling behaviour of sediment particles at volumetric concentrations of merely a few per cent. For example, the particle settling velocity in flows that carry 5% silt is reduced by at least 22%. These observations suggest that hindered settling greatly increases the efficiency of natural flows to transport sediment particles, but also particulate carbon and pollutants, such as plastics, over large distances. Abstract : A new equation for the hindered settling of suspensions of non‐cohesive particles in fluids is proposed, based on 548 data sets from a broad range of scientific disciplines.Hindered settling starts to influence the settling behaviour of sediment particles at volumetric concentrations of merely a few per cent, especially in silt to fine sand. This suggests that hindered settling greatly increases the efficiency of transport of sediment particles, particulate carbon and plastics over large distances.